Wireless-based infrastructures for indoor localization systems - Moreira, Ricardo Vilaça (2010)
The rapid evolution of Wireless technologies, speci cally in the area of Wireless Sensor Networks (WSN), has led to a growing demand for the availability of information anywhere, about anything. WSN are being widely used, for example, in domotic applications, partly due to their relatively low cost and their low energy consumption nature. These characteristics make this kind of networks very useful to ll some gaps in other applications, e.g. localization-related applications. This dissertation focuses, then, on the growing importance and demand for localization of people or objects and presents one of the possible approaches to the problem of indoor localization. By merging two di erent wireless technologies (IEEE 802.11 and IEEE 802.15.4), it is possible to make wireless communications more e cient for some applications. The merge is achieved by the creation of a Gateway, with support for both standards and near-transparent translation between them. This allows cheaper 802.15.4 devices to communicate with regular 802.11 TCP/IP (Transmission Control Protocol/Internet Protocol) based networks, giving space for inumerous applications, speci cally for localization purposes, which is the main goal of this project. The creation of the necessary hardware infrastructures and its respective control software, even though the solution may be used in a large range of applications, is more speci cally directed to comply with some of the requirements of the localization system to be created, eventually. So, in addition to the Gateways that make the translation between the two already referred standards, this project consists in the creation of Tags, small low-power and low-cost end-devices that are to be attached to the objects in need of localization features. These devices communicate with the Gateways by means of an 802.15.4 connection and indirectly advertise their location, by providing the signal strength of the connection. This data is computed and can be accessed in any personal computer with a web browser and a connection to the network.